Applying UTAUT in predicting ESL lecturers intention to use flipped learning - Abd Rahman, Siti Fatimah; Md Yunus, Melor; Hashim, Harwati (MDPI, 2021)
Flipped learning empowers learners to take an engaging role in learning while educators assist the learning process. The employment of flipped learning has been confirmed to enhance the teaching and learning of English as a second language in previous studies. This study aimed to explore the application of the unified theory of technology acceptance and use of technology towards ESL lecturers’ intention to use flipped learning. This study used a quantitative research framework where a set of online questionnaires was used in collecting the data. A total of 206 English as a second language lecturers from four different universities participated in this study. The data were analyzed using structural equation modeling. The result of this study indicates that only social influence is significant in predicting English as a second language lecturers’ intention to use the flipped learning approach. Furthermore, this study enriches the literature on 21st century education and the integration of technology in teaching and learning. In addition, this study could help educators and stakeholders in adapting or enhancing the flipped learning approach by distinguishing the distinct predictors of technology acceptance.